Analysis of energy flow and its intensity: A case study from China's 180 inter-provincial sectors - Zhengyang Li; Zhaocheng Li (Energy Strategy Reviews)
This study conducts a thorough quantitative analysis of energy flow and its intensity in 180 inter-provincial sectors of China. To achieve this, this study proposes two models based on the modified hypothetical extraction method and multi-regional input–output model, namely, an inter-regional sectoral energy consumption net-flow model and an inter-regional sectoral energy net-flow intensity model. The findings reveal that Construction in Shandong, Construction in Jiangsu, and Industry in Zhejiang are the top three energy receivers, with total net-input values of 6,054 × 104 ton of coal equivalent (tce), 5,259 × 104 tce, and 5,171 × 104 tce, respectively. Additionally, Industry in Inner Mongolia, Shandong, and Hebei are the top three energy suppliers, with total net-output values of 12,073 × 104 tce, 11,374 × 104 tce, and 10,455 × 104 tce, respectively. Furthermore, the study finds that the inter-provincial sectoral energy net-input intensity of Construction in Qinghai (−4.46 tce/ten thousand yuan), Xinjiang (−3.32 tce/ten thousand yuan), and Shanxi (−3.14 tce/ten thousand yuan) had the largest influence. In contrast, the inter-provincial sectoral energy net-output intensity of Industry in Qinghai (3.06 tce/ten thousand yuan), Industry in Xinjiang (2.95 tce/ten thousand yuan), and Transportation in Yunnan (2.39 tce/ten thousand yuan) have significant roles in China's 180 inter-provincial sectors.